2000
DOI: 10.3354/meps199185
|View full text |Cite
|
Sign up to set email alerts
|

Barnacle settlement:field experiments on the influence of larval supply, tidal level, biofilm quality and age on Balanus amphitrite cyprids

Abstract: A set of 3 field experiments lasting 24 h was conducted during April 1998 at the Duke University Marine Laboratory (Beaufort, North Carolina, USA) to: (1) assess the influence of larval supply, intertidal height, quantity and quality of biofilm and age of the larvae on the settlement of Balanus amphitrite Darwin and (2) examine the correspondence between small-scale planktonic distribution of larvae, the initial spatial pattern of newly settled larvae and the vertical distribution of adult barnacles. Precoloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 89 publications
(154 reference statements)
3
72
0
3
Order By: Relevance
“…Using a field experiment designed to study habitat selectivity, Olivier et al (2000) observed a positive correlation between Balanus ampitrite cyprid settlement and the nature of the biofilm on the settlement surface, with settling mainly occurring on surfaces free of detritus. Furthermore, these authors showed a significant decrease in cyprid settlement success with successive experiments over 6 d; this decrease was associated with a loss of habitat selectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a field experiment designed to study habitat selectivity, Olivier et al (2000) observed a positive correlation between Balanus ampitrite cyprid settlement and the nature of the biofilm on the settlement surface, with settling mainly occurring on surfaces free of detritus. Furthermore, these authors showed a significant decrease in cyprid settlement success with successive experiments over 6 d; this decrease was associated with a loss of habitat selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the physiological condition of these cyprids, representing their energy content and age, would be an interesting opportunity to demonstrate the role of larval physiology in controlling the habitat selection behaviour leading to permanent attachment in the field. Thus, in this study, we analyzed the energy status of cyprids collected during this earlier experiment (Olivier et al 2000) to test the hypothesis that habitat selectivity and settlement success relies more on the physiological condition of the larvae rather than on the supply of larvae. The physiological condition of the larvae was examined in relation to the abundance of both nonsettled and settled larvae, substrata of different quality and intertidal position.…”
Section: Introductionmentioning
confidence: 99%
“…So far, however, studies have been limited to the behavioural response of larvae to settlement cues. This has created a wealth of information on the environmental stimuli that B. amphitrite respond to during surface exploration (eg Rittschof et al 1984;Holmstro¨m et al 1992;O'Connor and Richardson 1998;Olivier et al 2000;Prendergast et al 2009;Aldred et al 2010) but the molecular mechanisms underlying these responses remain unclear. In recent years, Thiyagarajan and Qian (2008) have used a proteomics approach to investigate B. amphitrite development.…”
Section: Introductionmentioning
confidence: 99%
“…cannibalism), and larval physiology (age, competency, energy reserves) (Olivier et al, 2000;10 Qian et al, 2000;Marshall and Keough, 2003;Koehl et al, 2007;Tremblay et al, 2007) 11…”
mentioning
confidence: 99%